Heterotrophic Dinoflagellate Growth and Grazing Rates Reduced by Microplastic Ingestion - Fulfer, Victoria M.; Menden-Deuer, Susanne (Frontiers in Marine Science, 2021)
Microplastics are ubiquitous contaminants in marine ecosystems worldwide, threatening fisheries production, food safety, and human health. Ingestion of microplastics by fish and large zooplankton has been documented, but there are few studies focusing on single-celled marine predators, including heterotrophic dinoflagellates. In laboratory experiments, the heterotrophic dinoflagellate species Oxyrrhis marina and Gyrodinium sp. readily ingested both algal prey and polystyrene microplastic spheres (2.5–4.5 μm), while Protoperidinium sp. did not ingest microplastics. Compared to algae-only fed dinoflagellates, those that ingested microplastics had growth rates reduced by 25–35% over the course of 5 days. Reduced growth resulted in a 30–50% reduction of secondary production as measured as predator biomass. Ingestion rates of algal prey were also reduced in the microplastic treatments. When given a mixture of microplastics and algal prey, O. marina displayed a higher selectivity for algal prey than Gyrodinium sp. Observations in the coastal ocean showed that phylogenetically diverse taxa ingested microplastic beads, and thus heterotrophic dinoflagellates could contribute to trophic transfer of microplastics to higher trophic levels. The results of this study may suggest that continued increase in microplastic pollution in the ocean could lead to reduced secondary production of heterotrophic protists due to microplastic ingestion, altering the flow of energy and matter in marine microbial food webs.